MO189OUTCOMES OF AN ACCELERATED CITRATE ANTIGOAGULATED MEMBRANE SEPARATION PLASMA EXCHANGE ALGORITHM. (29th May 2021) - Halpin, Michael; Chen, Bonny; Singer, Richard
Abstract: Background and Aims: Plasma exchange is a standard therapy for some anti glomerular basement membrane disease and some types of renal transplant rejection. As with other extracorporeal therapies, anticoagulation is usually required. This study assessed the safety, efficacy and Calcium flux of an accelerated algorithm for regional citrate anticoagulation in membrane-based plasma exchange. Method: This was an observational study in patients receiving citrate anticoagulated, membrane-based, plasma exchange at the Canberra Hospital between July 2017 and May 2020. Data was collected prospectively using an electronic medical record and compared to data from our previously published algorithm which had used a slower blood pump speed. Results: There were 134 plasma exchange sessions performed during the observational period. Circuit clotting occurred in 4 sessions and 1 session was affected by symptomatic hypocalcaemia. A systemic ionised calcium <0.96 mmol/L was seen in 19.4% of sessions, which was a similar frequency to that seen in our previous algorithm. A systemic ionised Ca <0.81 mmol/L occurred in 4 sessions (all asymptomatic). This hypocalcaemia occurred towards the end of the sessions, after switching from albumin to fresh frozen plasma replacement fluid. Median treatment time was 135 minutes, compared to 219 minutes in our previously published algorithm. Mean net Ca gain/session was 7.7 ± 2.3 mmol. Conclusion: An accelerated algorithm for regional citrate anticoagulation achieves substantial time savings while maintaining efficacy and safety. The 4 episodes of systemic ionised calcium <0.81 mmol/L may have been due to recirculation of infused citrate but, probably more likely, are due to the additional citrate load imposed by use of fresh frozen plasma in these sessions. Future algorithms need to better account for the citrate load present in fresh frozen plasma.